QORAQALPOG’ISTON RESPUBLIKASI ELLIKQAL’A TUMANI ISHLAB CHIQARISH SOHALARINING RIVOJLANISHI - Iskenderov, A.; Kazbekov, O‘. (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of manufacturing branches of industry and agriculture in Ellikala region and the author shows the comparative indicators in these fields for several years. The author also studies the issues of the development of agriculture and ways of their decision.